EARLY FLOWERING 3 and Photoperiod Sensing in Brachypodium distachyon - Bouché, Frédéric; Woods, Daniel P.; Linden, Julie; Li, Weiya; Mayer, Kevin S.; Amasino, Richard M.; Périlleux, Claire (Frontiers in Plant Science, 2022)
The proper timing of flowering, which is key to maximize reproductive success and yield, relies in many plant species on the coordination between environmental cues and endogenous developmental programs. The perception of changes in day length is one of the most reliable cues of seasonal change, and this involves the interplay between the sensing of light signals and the circadian clock. Here, we describe a Brachypodium distachyon mutant allele of the evening complex protein EARLY FLOWERING 3 (ELF3). We show that the elf3 mutant flowers more rapidly than wild type plants in short days as well as under longer photoperiods but, in very long (20h) days, flowering is equally rapid in elf3 and wild type. Furthermore, flowering in the elf3 mutant is still sensitive to vernalization, but not to ambient temperature changes. Molecular analyses revealed that the expression of a short-day marker gene is suppressed in elf3 grown in short days, and the expression patterns of clock genes and flowering time regulators are altered. We also explored the mechanisms of photoperiodic perception in temperate grasses by exposing B. distachyon plants grown under a 12h photoperiod to a daily night break consisting of a mixture of red and far-red light. We showed that 2h breaks are sufficient to accelerate flowering in B. distachyon under non-inductive photoperiods and that this acceleration of flowering is mediated by red light. Finally, we discuss advances and perspectives for research on the perception of photoperiod in temperate grasses.